The effect of respiratory muscle training with CO2 breathing on cellular adaptation of mdx mouse diaphragm - Matécki, Stefan (Pergamon Press, 2005)
The aim of our study was to investigate the cellular mechanisms induced by hypercapnic stimulation of ventilation, during 6 weeks/30 min per day, in 10 mdx and 8 C57BL10 mice (10G0.2 months old). Ten mdx and eight C57BL10 mice served as control group. This respiratory training increases in vitro maximal tetanic tension of the diaphragm only in mdx mice. Western blot analysis of diaphragm showed: (1) an over-expression of a-dystrobrevin in mdx and C57BL10 training group compared to control group (8100G710 versus 6100G520 and 2800G400 versus 2200G250 arbitrary units); (2) a decrease in utrophin expression only in mdx training group compared to control group (2100G320 versus 3100G125 arbitrary units). Daily respiratory muscle training in mdx mice, induces a beneficial effect on diaphragm strength, with an over-expression of a-dystrobrevin. Further studies are needed to determine if, in absence of dystrophin, the over-expression of a-dystrobrevin could be interpreted as a possible pathway to improve function of dystrophic muscle.